2014
DOI: 10.1086/677554
|View full text |Cite
|
Sign up to set email alerts
|

Fast reaction of macroinvertebrate communities to stagnation and drought in streams with contrasting nutrient availability

Abstract: Small, permanent streams are at risk of becoming stagnant or intermittent because of hydrological changes induced by climate change, which can be further intensified by anthropogenic disruptions, such as water abstraction. Macroinvertebrate communities are vulnerable to such changes because they depend on stream hydromorphological regime. We conducted a fully controlled field experiment in 1 impacted and 1 unimpacted Danish lowland stream with contrasting nutrient availability. We used dams and diversions to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…These results reinforce findings of previous studies where diversity decreased with streamflow (Wooster, Miller, & DeBano, ). The negative correlation between drift diversity and streamflow may be a direct reflection of species presence in the benthic habitat, which is influenced by streamflow (Dewson et al, ; Hille et al, ; Kennedy et al, ; Walters & Post, ). Although numerous other mechanisms are plausible, streamflow is the underlying cause of each of them, suggesting that alterations to streamflow will typically result in changes to community diversity of invertebrate drift in rivers (Wooster et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results reinforce findings of previous studies where diversity decreased with streamflow (Wooster, Miller, & DeBano, ). The negative correlation between drift diversity and streamflow may be a direct reflection of species presence in the benthic habitat, which is influenced by streamflow (Dewson et al, ; Hille et al, ; Kennedy et al, ; Walters & Post, ). Although numerous other mechanisms are plausible, streamflow is the underlying cause of each of them, suggesting that alterations to streamflow will typically result in changes to community diversity of invertebrate drift in rivers (Wooster et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The low-flow phase was started on 28 August 2014 and lasted for 28 days. Here, the flow was reduced to simulate a flow event typical of lowland streams in Central European intensive agricultural landscapes in summer (Graeber, Gelbrecht, Pusch, Anlanger, & von Schiller, 2012;Graeber et al, 2015;Hille et al, 2014). The discharge was lowered from, on average, 5.2 L/s during the normal-flow phase to 1 L/s during the low-flow phase, rendering a current velocity reduction of 83%-93% in the run habitat (further statistics on the hydraulics in the different treatments are available in Appendices S1 and S2).…”
Section: Experimental Designmentioning
confidence: 99%
“…In the coastal climates of northern Europe, climate change‐mediated alterations in flow regimes in lowland streams are pronounced and periods with critically low flows are becoming more and more common during summer (Arnell, ). Furthermore, worldwide stream ecosystems are affected by high water abstraction, high loads of fine sediments and elevated nutrient concentrations due to agricultural activities (Graeber, Pusch, Lorenz, & Brauns, ; Hille et al., ; Piggott, Salis, Lear, Townsend, & Matthaei, ; Townsend, Uhlmann, & Matthaei, ; Wagenhoff, Lange, Townsend, & Matthaei, ). Therefore, multiple stress in lowland agricultural streams is a widespread phenomenon that strongly affects biological stream communities, including benthic algae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We manipulated flow reduction in two permanent, lowland forested streams and showed that flow reduction strongly reduced dissolved oxygen, among other environmental changes, to concentrations known to negatively influence the survival of stream biological communities (Connolly et al, 2004). Previous studies on the effects of natural low flows and artificially reduced flows (without complete cessation of flow) on stream invertebrates found no evidence that low or reduced flows affect dissolved O 2 concentrations (see review in Dewson et al, 2007;Hille et al, 2014). This lack of evidence was attributed to the fact that measurements were obtained during day hours; however, low oxygen values have been occasionally recorded (James et al, Verdonschot et al (2015) found anoxia in remnant pools during flow reduction.…”
Section: Environmental Impactmentioning
confidence: 99%